S-RNases from self-incompatible and -compatible apple cultivars: Purification, cloning, enzymic properties, and pollen tube growth inhibitory activity - Katoh, N. (Hirosaki Univ., Aomori (Japan). Faculty of Agriculture and Life Science); Goto, K; Asano, J; Fukushima, K; Yamada, K; Kasai, A; Li, T.Z; Takanoha, M; Miyairi, K; Okuno, T (Bioscience, biotechnology, and biochemistry, 2002)
Four S-RNases (RNase associated with self-incom-patibility) were purified from the styles of two apple cultivars (Malus domestica), a self-incompatible cv., Starking Delicious (SD), and a self-compatible cv., Megumi (MG). Each cultivar produced two S-RNases and their enzymatic properties such as specific activity, pH optimum, thermal stability, and molecular mass, were characterized. The four S-RNases inhibited the tube growth of apple pollen in an in vitro bioassay at 25 micro g/ml (1.0 micro M), but did not distinguish self from non-self pollen. The cDNAs of four S-RNases were cloned, and the nucleotide and deduced amino acid sequences were analyzed. The nucleotide sequence of SD-Se RNase was a new one and the other was identical to that of Sc-RNase of cv. Fuji. In MG one was identical to the sequence of SD-Sc RNase and the other to that of Sa-RNase of cv. Golden Delicious except for one base. From results of the isolation amounts and the Western blot analysis for stylar crude extracts the amount of S-RNases in MG was apparently less than that in SD.